Report: proposed upgrading of Kompleks Pengembangan Tenun Pahang Diraja Sultan Haji Ahmad Shah for Perbadanan Kemajuan Negeri Pahang (Pknp) at Kampung Sungai Soi, Jalan Kempadang Perdana 1, 25150 Kuantan, Pahang / Ahmad Shafiq Fiqri Rosnari - Rosnari, Ahmad Shafiq Fiqri (Faculty of Architecture, Planning and Surveying, 2011)
Malaysia are known as a country that rich with their cultural and custom especially in traditional fabric industries . People only know about batik and songket that be famous at Kelantan and Terengganu. Pahang also have their own masterpies that can be market to all over the world. They called it Tenun Pahang Diraja. The Tenun Pahang Diraja, a type of woven silk fabric popular in Pahang, has recorded sales of RM1.35 million last year and efforts to expand the industry need to be stepped up. This fabric is quite similar with songket because of their technique to produce. It have simple geometric pattern. It also more comfort and light to wear. The proposal for this project is Proposed Upgrading of Kompleks Pengembangan Tenun Pahang Diraja Sultan Haji Ahmad Shah. The proposed site is located at Kampung Sungai Soi, Jalan Kempadang Perdana 1, 25150 Kuantan, Pahang, known as a famous tourism zone especially near with Tanjung Sepat. It is a new complex was built in year 2000. Perbadanan Kemajuan Negeri Pahang (PKNP) are responsible to organize this complex and support our local weavers especially at Pahang. This complex are focusing to produce more contemporary design but in the same time retain traditional and original technique to compete with the local and international market. The design in this project more focus to upgrade new space planning especially at multifunction area, showroom and tenun workshop that have many problem to solve. This proposal also to create an exclusive interior, make a standard and quality suitable with the name award ‘Diraja’ give by The Royal of Pahang.